2021
DOI: 10.1177/17475198211056285
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrochemical performance of NiO-doped TiO2 nanotubes prepared by an impregnation–calcination method

Abstract: To improve the photocatalytic activity of TiO2, a series of NiO–TiO2 nanotubes (NTbs) is prepared by impregnating TiO2 nanotubes in a solution of NiCl2·6H2O at different concentrations. Self-organized TiO2 nanotubes are prepared by a two-step anodization process. Scanning electron microscopy images show that large particle agglomerates are formed for higher precursor concentrations, and X-ray energy-dispersive spectroscopy results indicate that the atomic percentages of Ni in the NiO–TiO2 NTbs prepared with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…5), which may due to the adsorption desorption reaction mechanism during the photodegradation process on the Cu 2 O–TiO 2 NT surface, which is consistent with our previous work. 1,27 Fig. 6(b) shows the incident photon-to-electron conversion efficiency (IPCE) under monochromatic illumination, which was calculated using the following formula:where j p is the photocurrent density, P is the incident light density per unit area, and λ is the incident light wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), which may due to the adsorption desorption reaction mechanism during the photodegradation process on the Cu 2 O–TiO 2 NT surface, which is consistent with our previous work. 1,27 Fig. 6(b) shows the incident photon-to-electron conversion efficiency (IPCE) under monochromatic illumination, which was calculated using the following formula:where j p is the photocurrent density, P is the incident light density per unit area, and λ is the incident light wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…23–26 Wang et al deposited NiO nanoparticles (NPs) on TiO 2 NTs using a direct impregnation–calcination method and achieved improved photocatalytic performance. 27 Liu et al designed and prepared a novel TiO 2 /MoC–Mo 2 C@C heterostructure via a calcination method and realized enhanced photocatalytic activity in water splitting, thus achieving a high H 2 generation rate of 918 μmol h −1 g −1 . 28 Further, Li et al reported an improved H 2 production rate of 24.83 μmol h −1 g −1 for a TiO 2 catalyst doped with Cu 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…However, TiO 2 can only be stimulated by UV light, which accounts for only 3–5% of solar energy radiation, because of its large band gap, further causing quick recombination of photoinduced electron-hole pairs as well as inefficient charge carrier separation [ 11 ]. Therefore, various methods have been used to improve the PEC performance and photocatalytic activity of TiO 2 , including morphology modification [ 12 , 13 , 14 ], synthesis of composite heterojunctions with other materials [ 15 ], ion doping [ 16 , 17 ], facet engineering [ 18 ], and cocatalyst addition [ 19 ].…”
Section: Introductionmentioning
confidence: 99%